De novo mutations of KIAA2022 in females cause intellectual disability and intractable epilepsy. Issue 12 (29th June 2016) - de Lange, Iris M; Helbig, Katherine L; Weckhuysen, Sarah; Møller, Rikke S; Velinov, Milen; Dolzhanskaya, Natalia; Marsh, Eric; Helbig, Ingo; Devinsky, Orrin; Tang, Sha; Mefford, Heather C; Myers, Candace T; et al.
Abstract : Background: Mutations in the KIAA2022 gene have been reported in male patients with X-linked intellectual disability, and related female carriers were unaffected. Here, we report 14 female patients who carry a heterozygous de novo KIAA2022 mutation and share a phenotype characterised by intellectual disability and epilepsy. Methods: Reported females were selected for genetic testing because of substantial developmental problems and/or epilepsy. X-inactivation and expression studies were performed when possible. Results: All mutations were predicted to result in a frameshift or premature stop. 12 out of 14 patients had intractable epilepsy with myoclonic and/or absence seizures, and generalised in 11. Thirteen patients had mild to severe intellectual disability. This female phenotype partially overlaps with the reported male phenotype which consists of more severe intellectual disability, microcephaly, growth retardation, facial dysmorphisms and, less frequently, epilepsy. One female patient showed completely skewed X-inactivation, complete absence of RNA expression in blood and a phenotype similar to male patients. In the six other tested patients, X-inactivation was random, confirmed by a non-significant twofold to threefold decrease of RNA expression in blood, consistent with the expected mosaicism between cells expressing mutant or normal KIAA2022 alleles. Conclusions: Heterozygous loss of KIAA2022 expression is a cause of intellectual disability in females. Compared with its hemizygous male counterpart, the heterozygous female disease has less severe intellectual disability, but is more often associated with a severe and intractable myoclonic epilepsy.